Thermally conductive adhesive composition and manufacturing method thereof, thermally conductive film-like adhesive, and semiconductor package using thermally conductive film-like adhesive and manufacturing method thereof

JP7646089B2Active Publication Date: 2025-03-14FURUKAWA ELECTRIC CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024532565
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-02-28
Filing Date
2024-02-16
Publication Date
2025-03-14
Estimated Expiration
2044-02-16

AI Technical Summary

Benefits of technology

【0012】 本発明の熱伝導性接着剤用組成物は、窒化物セラミックスフィラーをより小粒径としながらも、得られるフィルム状接着剤においてフィラー同士の凝集を抑えることができ、フィルム状接着剤の溶融粘度の上昇も抑えることができる。本発明の熱伝導性接着剤用組成物の製造方法は、本発明の熱伝導性接着剤用組成物の調製方法として好適である。 また、本発明の熱伝導性フィルム状接着剤は、より小粒径の窒化物セラミックスフィラーを含有しながらも、フィラー同士の凝集を抑えることができ、接着剤の溶融粘度の上昇も抑えることができる。 また、本発明の半導体パッケージは、上記の優れた特性を有する熱伝導性フィルム状接着剤を介して半導体チップが接着され、接着面のボイドが抑えられ、熱の放出性に優れる。本発明の半導体パッケージの製造方法は、本発明の半導体パッケージの製造方法として好適である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007646089000004
    Figure 0007646089000004
  • Figure 0007646089000005
    Figure 0007646089000005
  • Figure 0007646089000006
    Figure 0007646089000006
Patent Text Reader

Abstract

Disclosed is a composition for thermally conductive adhesives, the composition containing an epoxy resin (A), an epoxy resin curing agent (B), a polymer component (C) and a nitride ceramic filler (D), wherein: the nitride ceramic filler (D) satisfies condition (1) the average particle diameter as determined by image analysis is 0.1-2.5 µm, condition (2) the circularity as determined by image analysis is 0.7 or more, and condition (3) the maximum particle diameter as determined by image analysis is 10.0 µm or less; and the proportion of the nitride ceramic filler (D) in the sum of the contents of the epoxy resin (A), the epoxy resin curing agent (B), the polymer component (C) and the nitride ceramic filler (D) is 25-65% by volume. Also disclosed are: a thermally conductive film-like adhesive; a semiconductor package; and production methods for the composition for thermally conductive adhesives, the thermally conductive film-like adhesive and the semiconductor package.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermally conductive adhesive composition and a method for producing the same, a thermally conductive film-like adhesive, and a semiconductor package using the thermally conductive film-like adhesive and a method for producing the same. [Background technology]

[0002] In recent years, as electronic devices become smaller and more sophisticated and multifunctional, the semiconductor packages mounted inside them are also becoming more sophisticated and multifunctional, and semiconductor wafer wiring rules are becoming finer. Along with this trend toward more sophisticated and multifunctional devices, stacked MCPs (Multi Chip Packages), in which semiconductor chips are stacked in multiple layers, have become widespread and are mounted in memory packages for mobile phones and mobile audio devices. In addition, as mobile phones and other devices become more multifunctional, packages are becoming denser and more highly integrated. Accordingly, the trend toward stacking multiple layers of semiconductor chips is progressing even further.

[0003] In the manufacturing process of such memory packages, a film-like adhesive (die attach film) is used to bond the wiring board and the semiconductor chip, and also to bond between semiconductor chips (so-called die attach). As chips are stacked in multiple layers, there is a demand for thinner die attach films. In addition, wafer wiring rules have been getting finer in recent years, making it easier for heat to be generated on the surface of semiconductor elements. For this reason, in order to make it easier for heat to escape outside the package, these die attach films are blended with thermally conductive fillers (inorganic filling materials) to achieve high thermal conductivity.

[0004] The thin thermally conductive die attach film is designed as a film-like adhesive highly filled with thermally conductive fillers having small particle diameters. However, when the particle diameter of the filler is small, the specific surface area becomes large, so that the interaction between the fillers becomes strong, and when the filler is mixed with the resin in the production of the die attach film, the filler is likely to aggregate. As a result, aggregates tend to be scattered on the surface of the obtained thin thermally conductive die attach film. In addition, the thermally conductive filler having a small particle diameter tends to reduce the fluidity of the die attach film and increase the melt viscosity of the die attach film. Therefore, a thin thermally conductive die attach film highly filled with a thermally conductive filler having a small particle diameter is likely to cause problems such as a decrease in adhesive strength and a decrease in heat dissipation when it is adhered to the back surface of a semiconductor chip or a wiring board as an adherend, as it may involve voids or not be able to be fully filled into the uneven parts of the wiring board.

[0005] Regarding thermally conductive die attach films, for example, Patent Document 1 describes an adhesive composition that contains specific amounts of epoxy resin (A), epoxy resin curing agent (B), polymer component (C), and inorganic filler (D), in which the average particle size (d50) of this inorganic filler (D) is 0.1 to 3.5 μm, and the ratio of the particle size (d90) at a cumulative distribution frequency of 90% to this average particle size (d50) is 5.0 or less. According to the technology described in Patent Document 1, by preparing a film-like adhesive using this adhesive composition, it is possible to suppress the generation of voids after the die attachment process even in the form of a thin film, and to obtain a film-like adhesive that has excellent adhesive strength with the adherend and excellent thermal conductivity. Furthermore, Patent Document 2 describes a heat dissipating film-like adhesive that contains two or more types of thermally conductive fillers with different Mohs hardness and that causes blade wear during a dicing process of 50 μm / m or less. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2021 / 033368 [Patent Document 2] Patent Publication No. 2019-21829 Summary of the Invention [Problem to be solved by the invention]

[0007] To increase the thermal conductivity of film-like adhesives, nitride ceramics (ceramics containing nitrogen), such as aluminum nitride, which has high thermal conductivity, are seen as promising filler materials. Although various commercial products are available as fine nitride ceramic filler materials, in order to further improve the performance of the resulting film-like adhesives, technology is required to effectively suppress the aggregation of the above-mentioned fillers and the increase in the melt viscosity of the film-like adhesives.

[0008] The present invention has been made in consideration of the problems associated with the above-mentioned conventional technology, and has an objective of providing a thermally conductive film-like adhesive that uses a nitride ceramic filler material (nitride ceramic filler), in which the nitride ceramic filler has a smaller particle size while suppressing aggregation between fillers in the film-like adhesive and suppressing an increase in the melt viscosity of the film-like adhesive, as well as a thermally conductive adhesive composition and a method for producing the same that are suitable for forming this thermally conductive film-like adhesive. Another object of the present invention is to provide a semiconductor package using the thermally conductive film-like adhesive having the above-mentioned excellent properties, and a method for manufacturing the same. [Means for solving the problem]

[0009] The inventors of the present invention have conducted extensive research to solve the above problems, and as a result have discovered that when a nitride ceramic filler is subjected to a crushing and disintegration process to produce smaller particle size fillers, the circularity of the filler increases, the interaction between the filler particles weakens, and aggregation is suppressed, and an increase in the melt viscosity of the resulting film-like adhesive is effectively suppressed, which is the opposite of the general phenomenon previously known (the specific surface area increases with particle size reduction, and the interaction between the filler particles strengthens).The present invention was completed based on these findings and through further investigation. That is, the above-mentioned object of the present invention is achieved by the following means.

[0010] [1] A thermally conductive adhesive composition comprising an epoxy resin (A), an epoxy resin curing agent (B), a polymer component (C) and a nitride ceramic filler (D), The nitride ceramic filler (D) satisfies the following conditions (1) to (3), A thermally conductive adhesive composition, wherein the proportion of the nitride ceramic filler (D) in the total content of the epoxy resin (A), the epoxy resin curing agent (B), the polymer component (C) and the nitride ceramic filler (D) is 25 to 65 volume %. (1) The average particle size determined by image analysis is 0.1 to 2.5 μm. (2) The image analysis circularity is 0.7 or more. (3) The maximum particle size determined by image analysis is 10.0 μm or less. [2] The thermally conductive adhesive composition according to [1], wherein when a film-like adhesive obtained from the adhesive composition is heated from 25°C at a rate of 5°C / min, the melt viscosity at 70°C is 15,000 to 50,000 Pa s. [3] The thermally conductive adhesive composition according to [1] or [2], wherein when a film-like adhesive obtained from the adhesive composition is heated from 25°C at a rate of 5°C / min, the melt viscosity at 120°C is 500 to 10,000 Pa s. [4] The thermally conductive adhesive composition according to any one of [1] to [3], wherein a film-like adhesive obtained from the adhesive composition gives a cured product having a thermal conductivity of 1.0 W / m K or more after thermal curing. [5] The thermally conductive adhesive composition according to any one of [1] to [4], wherein the nitride ceramic filler (D) is a product that has been subjected to a pulverization or crushing treatment. [6] A method for producing a thermally conductive adhesive composition according to any one of [1] to [5], comprising subjecting a nitride ceramic filler to a pulverization and crushing treatment to obtain the nitride ceramic filler (D) satisfying the above conditions (1) to (3), and using this nitride ceramic filler (D) to obtain the thermally conductive adhesive composition. [7] A thermally conductive film-like adhesive obtained from the thermally conductive adhesive composition according to any one of [1] to [5]. [8] The thermally conductive film-like adhesive according to [7], which has a thickness of 1 to 10 μm. [9] A dicing / die attach film obtained by laminating a dicing film and the thermally conductive film-like adhesive described in [7] or [8].

[10] A semiconductor package in which a semiconductor chip and a wiring board, or semiconductor chips are bonded together, with a thermoset of the thermally conductive film-like adhesive described in [7] or [8].

[11] A first step of providing an adhesive layer by thermocompression bonding the thermally conductive film-like adhesive according to [7] or [8] to a back surface of a semiconductor wafer having at least one semiconductor circuit formed on a front surface thereof, and providing a dicing film via the adhesive layer; a second step of dicing the semiconductor wafer and the adhesive layer together to obtain a semiconductor chip with an adhesive layer on the dicing film, the semiconductor chip comprising an adhesive piece and a semiconductor chip; a third step of peeling the semiconductor chip with the adhesive layer from the dicing film and thermocompression bonding the semiconductor chip with the adhesive layer and a wiring substrate via the adhesive piece; a fourth step of thermally curing the adhesive layer; A method for manufacturing a semiconductor package, comprising:

[12] The method for manufacturing a semiconductor package described in

[11] , wherein the first step is a step of thermocompression bonding the dicing die attach film described in [9] to the back surface of the semiconductor wafer.

[0011] In the present invention, a numerical range expressed using "to" means a range including the numerical values ​​before and after "to" as the lower and upper limits. In the present invention, the term "(meth)acrylic" refers to either or both of acrylic and methacrylic. The same applies to (meth)acrylate. Effect of the Invention

[0012] The thermally conductive adhesive composition of the present invention can suppress the aggregation of the fillers in the resulting film-like adhesive while making the nitride ceramic filler have a smaller particle size, and can also suppress an increase in the melt viscosity of the film-like adhesive. The method for producing the thermally conductive adhesive composition of the present invention is suitable as a method for preparing the thermally conductive adhesive composition of the present invention. Furthermore, even when the thermally conductive film-like adhesive of the present invention contains a nitride ceramic filler with a smaller particle size, it is possible to suppress the aggregation of the fillers and also to suppress an increase in the melt viscosity of the adhesive. In addition, in the semiconductor package of the present invention, a semiconductor chip is bonded via the thermally conductive film-like adhesive having the above-mentioned excellent properties, voids on the bonding surface are suppressed, and the semiconductor package has excellent heat dissipation properties. The method for manufacturing the semiconductor package of the present invention is suitable as the method for manufacturing the semiconductor package of the present invention. [Brief description of the drawings]

[0013] [Figure 1]FIG. 1 is a schematic vertical cross-sectional view showing a preferred embodiment of the first step of the method for producing a semiconductor package of the present invention. [Diagram 2] FIG. 2 is a schematic vertical sectional view showing a preferred embodiment of the second step of the method for producing a semiconductor package of the present invention. [Diagram 3] FIG. 3 is a schematic vertical cross-sectional view showing a preferred embodiment of the third step of the method for producing a semiconductor package of the present invention. [Figure 4] FIG. 4 is a schematic vertical cross-sectional view showing a preferred embodiment of a step of connecting bonding wires in the method for producing a semiconductor package of the present invention. [Diagram 5] FIG. 5 is a schematic vertical cross-sectional view showing a multi-layer stacking embodiment of the method for producing a semiconductor package of the present invention. [Figure 6] FIG. 6 is a schematic vertical cross-sectional view showing another multi-layer stacking embodiment of the method for producing a semiconductor package of the present invention. [Figure 7] FIG. 7 is a schematic vertical cross-sectional view showing a preferred embodiment of a semiconductor package manufactured by the semiconductor package manufacturing method of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] <<Adhesive composition>> The thermally conductive adhesive composition of the present invention (hereinafter also referred to as the adhesive composition of the present invention) is a composition suitable for forming the thermally conductive film-like adhesive of the present invention (hereinafter also referred to as the film-like adhesive of the present invention). The adhesive composition of the present invention contains an epoxy resin (A), an epoxy resin curing agent (B), a polymer component (C) and a nitride ceramic filler (D), The nitride ceramic filler (D) satisfies the following conditions (1) to (3), The proportion of the nitride ceramic filler (D) in the total content of the epoxy resin (A), the epoxy resin curing agent (B), the polymer component (C) and the nitride ceramic filler (D) is 25 to 65 volume %. (1) The average particle size determined by image analysis is 0.1 to 2.5 μm. (2) The image analysis circularity is 0.7 or more. (3) The maximum particle size determined by image analysis is 10.0 μm or less.

[0015] Hereinafter, in this specification, the epoxy resin (A) may be referred to as component (A), the epoxy resin curing agent (B) as component (B), the polymer component (C) as component (C), and the nitride ceramic filler (D) as component (D).

[0016] In the present invention, the image analysis average particle size means the average value of the projected area circle equivalent diameters of each particle in the observation field obtained by image analysis, and the image analysis maximum particle size means the maximum particle size among the projected area circle equivalent diameters of each particle in the observation field obtained by image analysis. The image analysis is carried out by placing 1.0 g of the nitride ceramic filler (dried product) on a glass plate and using an image analysis particle size distribution measuring device (Portable PITA, manufactured by Seishin Enterprise Co., Ltd.). The conditions for image analysis are as follows. Camera: 250x magnification, autofocus (AF) camera Observation field of view (measurement area): 679.428μm x 905.904μm Number of observation fields: 1 Image processing software: OpenCV (Open Source Computer Vision Library) Measured particle size: 0.1~10000μm Roughness: 0.9 or more Threshold:Auto When observed under the above conditions, approximately 1500 particles of nitride ceramic filler are observed in the observation field. Particles that overlap the outline of the observation field (particles that cannot be observed in their entirety) are excluded from the data. Particles that are clearly overlapping in the observation field and cannot be observed in their entirety are also excluded from the data. Ultimately, the number of particles from which data is obtained is approximately 1300. In the above image analysis, data is usually obtained for 1000 or more particles. The image analysis circularity means the average value of the circularity of each particle in the observation field obtained by the image analysis. The circularity of each particle is a value calculated by the following formula based on the projected area and perimeter of each particle. The perimeter is measured using the image processing software OpenCV. Circularity = 4π × projected area of ​​particle (μm 2 ) / (particle perimeter (μm)) 2

[0017] In the adhesive composition of the present invention, the shape of the nitride ceramic filler is controlled so that the image analysis average particle size is 0.1 to 2.5 μm, the image analysis circularity is 0.7 or more, and the image analysis maximum particle size is 10.0 μm or less, as specified in the above (1) to (3). The above shapes (1) to (3) are different from the shapes of commercially available nitride ceramic fillers, and are realized, for example, by crushing and disintegrating commercially available nitride ceramic fillers. Furthermore, in the adhesive composition of the present invention, the ratio of the nitride ceramic filler (D) to the total content of the epoxy resin (A), the epoxy resin curing agent (B), the polymer component (C), and the nitride ceramic filler (D) is controlled to 25 to 65% by volume. As a result, when forming a film-like adhesive, it is possible to suppress the aggregation of the nitride ceramic filler due to mixing with the resin component containing the epoxy resin (A) and the polymer component (C), and it is possible to suppress the melt viscosity of the obtained film-like adhesive, and it is possible to obtain a high-performance thermally conductive film-like adhesive. The reason for this is presumably due to the hardness of the nitride ceramic filler. One of the reasons is that the nitride ceramic filler is subjected to a crushing and disintegration process, which causes the fillers to collide with each other, which reduces the corners and increases the circularity, and even if the particle size is reduced, the specific surface area does not increase, but rather tends to decrease. As described above, the film-like adhesive obtained from the adhesive composition of the present invention can suppress the generation of aggregates and the increase in melt viscosity even though the nitride ceramic filler has a smaller particle size, and as a result, even in a thin film-like adhesive, the generation of voids in the die attachment process can be sufficiently suppressed.

[0018] Considering the reactivity of the epoxy resin (A) and the epoxy resin curing agent (B), the adhesive composition of the present invention is preferably stored refrigerated at or below 10° C. The film-like adhesive of the present invention described below can also be stored under similar conditions.

[0019] Furthermore, by forming a film-like adhesive using the adhesive composition of the present invention, it is possible to reduce the amount of wear of the processing blade when used as a die attachment film in a dicing process. In the manufacturing process of a semiconductor package, it is preferable that the wear rate of the processing blade caused by the die attachment film is small in the so-called dicing process in which the die attachment film and the semiconductor wafer on which the semiconductor element is formed are cut together. In the adhesive composition of the present invention, the particle size of the nitride ceramic filler is smaller and has a higher circularity, so that wear of the processing blade can be suppressed.

[0020] There is no particular limitation on the method for controlling the image analysis average particle size, image analysis circularity, and image analysis maximum particle size of the nitride ceramic filler so that they satisfy the conditions (1) to (3). For example, they can be controlled by subjecting the nitride ceramic filler to a pulverization / crushing treatment described later.

[0021] The image analysis average particle size of the nitride ceramic filler is preferably 0.5 to 2.5 μm, more preferably 0.8 to 2.5 μm, more preferably 1.0 to 2.0 μm, even more preferably 1.1 to 2.0 μm, still more preferably 1.2 to 1.8 μm, and particularly preferably 1.2 to 1.6 μm. When the nitride ceramic filler is boron nitride, the image analysis average particle size can be 0.5 to 1.8 μm. The image analysis circularity of the nitride ceramic filler is preferably from 0.75 to 1.0, more preferably from 0.80 to 0.99, further preferably from 0.82 to 0.99, and particularly preferably from 0.85 to 0.99. The maximum particle size of the nitride ceramic filler as determined by image analysis is preferably 9.0 μm or less, more preferably 8.8 μm or less, and even more preferably 8.0 μm or less. It is particularly preferably 7.0 μm or less. There is no particular lower limit, but a value of 3.0 μm or more is practical.

[0022] In the present invention, the proportion of the nitride ceramic filler (D) in the total content of the epoxy resin (A), the epoxy resin curing agent (B), the polymer component (C) and the nitride ceramic filler (D) is 25 to 65 volume %. By setting the content of the nitride ceramic filler (D) within the above range, it is possible to impart the desired thermal conductivity and melt viscosity to the film-like adhesive. The proportion of the nitride ceramic filler (D) in the total content of components (A) to (D) is preferably 25 to 60 volume %, more preferably 30 to 55 volume %, even more preferably 35 to 55 volume %, and even more preferably 30 to 50 volume %. The content (volume %) of the nitride ceramic filler (D) can be calculated from the mass content and specific gravity of each of the components (A) to (D). In the present invention, in calculating the volume %, the specific gravity of each of the components (A) to (C) is set to 1.2, and the specific gravity of the component (D) is calculated using the true specific gravity.

[0023] Hereinafter, each component contained in the adhesive composition will be described in more detail.

[0024] <Epoxy resin (A)> The epoxy resin (A) can be used without any particular limitation as long as it is a thermosetting resin having an epoxy group, and may be liquid, solid, or semi-solid. In the present invention, the term "liquid" refers to a resin having a softening point of less than 25°C, the term "solid" refers to a resin having a softening point of 60°C or higher, and the term "semi-solid" refers to a resin having a softening point between the softening point of the liquid and the softening point of the solid (25°C or higher and less than 60°C). The epoxy resin (A) used in the present invention preferably has a softening point of 100°C or lower, from the viewpoint of obtaining a film-like adhesive that can reach a low melt viscosity in a suitable temperature range (for example, 60 to 120°C). In the present invention, the softening point is a value measured by a softening point test (ring and ball method) method (measurement conditions: in accordance with JIS-2817).

[0025] In the epoxy resin (A) used in the present invention, the crosslink density of the cured product is increased, and as a result, the contact probability between the blended nitride ceramic fillers (D) is increased and the contact area is increased, so that a higher thermal conductivity can be obtained. From this viewpoint, the epoxy equivalent is preferably 500 g / eq or less, and more preferably 150 to 450 g / eq. In the present invention, the epoxy equivalent refers to the number of grams (g / eq) of a resin containing 1 gram equivalent of epoxy groups. The weight average molecular weight of the epoxy resin (A) is usually preferably less than 10000, more preferably not more than 5000. There is no particular restriction on the lower limit, but a value of 300 or more is practical. The weight average molecular weight is a value obtained by GPC (Gel Permeation Chromatography) analysis. (The same applies to other resins below unless otherwise specified.)

[0026] Examples of the skeleton of the epoxy resin (A) include phenol novolac type, orthocresol novolac type, cresol novolac type, dicyclopentadiene type, biphenyl type, fluorene bisphenol type, triazine type, naphthol type, naphthalene diol type, triphenylmethane type, tetraphenyl type, bisphenol A type, bisphenol F type, bisphenol AD ​​type, bisphenol S type, trimethylolmethane type, etc. Among these, from the viewpoint of obtaining a film-like adhesive having low crystallinity of the resin and good appearance, the triphenylmethane type, bisphenol A type, cresol novolac type, and orthocresol novolac type are preferred.

[0027] The content of the epoxy resin (A) is preferably 3 to 40 parts by mass, more preferably 5 to 40 parts by mass, more preferably 8 to 35 parts by mass, even more preferably 10 to 30 parts by mass, and particularly preferably 20 to 30 parts by mass, based on 100 parts by mass of the total content of the components constituting the film-like adhesive (specifically, the components other than the solvent, i.e., the solid content) in the adhesive composition of the present invention. By making the content equal to or greater than the above-mentioned preferable lower limit, the thermal conductivity of the film-like adhesive can be improved. On the other hand, by making the content equal to or less than the above-mentioned preferable upper limit, the generation of oligomer components can be suppressed, and the film state (film tackiness, etc.) can be made less likely to change due to a slight change in temperature.

[0028] <Epoxy resin hardener (B)> As the epoxy resin curing agent (B), any curing agent such as amines, acid anhydrides, polyhydric phenols, etc. In the present invention, it is preferable to use a latent curing agent, from the viewpoint that the epoxy resin (A) and the polymer component (C) described below have a low melt viscosity, exhibit curing properties at a high temperature exceeding a certain temperature, have fast curing properties, and can be stored for a long period of time at room temperature, and a thermally conductive adhesive composition having high storage stability can be obtained. Examples of the latent curing agent include dicyandiamide compounds, imidazole compounds, curing catalyst composite polyphenol compounds, hydrazide compounds, boron trifluoride-amine complexes, amine imide compounds, polyamine salts, and modified and microcapsulated versions of these. In the present invention, it is more preferable to use an imidazole compound from the viewpoint of adjusting the melt viscosity at 70°C and the melt viscosity at 120°C of the thermally conductive film-like adhesive to satisfy the above-mentioned preferred ranges. These may be used alone or in combination of two or more.

[0029] The content of the epoxy resin curing agent (B) relative to 100 parts by mass of the epoxy resin (A) is preferably 0.5 to 100 parts by mass, more preferably 1 to 80 parts by mass. By making the content equal to or more than the above-mentioned preferable lower limit, the curing time can be shortened, while by making the content equal to or less than the above-mentioned preferable upper limit, the excess curing agent remains in the film-like adhesive, and the residual curing agent adsorbs moisture, thereby reducing defects in a reliability test after the film-like adhesive is incorporated into a semiconductor.

[0030] <Polymer component (C)> The polymer component (C) may be any component that, when a film-like adhesive is formed, suppresses the film tackiness (the property that the film state is easily changed even by a slight change in temperature) at room temperature (25 ° C.) and imparts sufficient adhesiveness and film-forming properties (film-forming properties). Examples of the polymer component (C) include natural rubber, butyl rubber, isoprene rubber, chloroprene rubber, ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylic acid ester copolymer, polybutadiene resin, polycarbonate resin, thermoplastic polyimide resin, polyamide resin such as 6-nylon and 6,6-nylon, phenoxy resin, (meth)acrylic resin, polyester resin such as polyethylene terephthalate and polybutylene terephthalate, polyamideimide resin, fluororesin, polyurethane resin, etc. These polymer components (C) may be used alone or in combination of two or more. As the polymer component (C), at least one of phenoxy resin, (meth)acrylic resin, and polyurethane resin is preferable.

[0031] The weight average molecular weight of the polymer component (C) is preferably at least 10000. There is no particular upper limit, but a value of 5,000,000 or less is practical. The weight average molecular weight of the polymer component (C) is a value determined by GPC (gel permeation chromatography) in terms of polystyrene. Hereinafter, the specific weight average molecular weight of the polymer component (C) has the same meaning. The glass transition temperature (Tg) of the polymer component (C) is preferably less than 100° C., more preferably less than 90° C. The lower limit is preferably 0° C. or higher, more preferably 10° C. or higher. The glass transition temperature of the polymer component (C) is a glass transition temperature measured by DSC at a heating rate of 0.1° C. / min. Hereinafter, the specific glass transition temperature of the polymer component (C) has the same meaning. In the present invention, among the epoxy resin (A) and the polymer component (C), resins that may have epoxy groups, such as phenoxy resins, are classified as follows: resins with an epoxy equivalent of 500 g / eq or less are classified as epoxy resins (A), and those not corresponding to this are classified as polymer components (C).

[0032] (Phenoxy resin) Phenoxy resin is preferred as the polymer component (C) because it has a similar structure to the epoxy resin (A) and is therefore compatible with it. When the phenoxy resin is contained, it can also exhibit excellent adhesive properties. The phenoxy resin can be obtained by a conventional method, for example, by reacting a bisphenol or biphenol compound with an epihalohydrin such as epichlorohydrin, or by reacting a liquid epoxy resin with a bisphenol or biphenol compound.

[0033] The weight average molecular weight of the phenoxy resin is preferably 10,000 or more, and more preferably 10,000 to 100,000. Furthermore, the amount of epoxy groups remaining in the phenoxy resin in small amounts is preferably 5000 g / eq or more in terms of epoxy equivalent.

[0034] The glass transition temperature (Tg) of the phenoxy resin is preferably less than 100° C., more preferably less than 90° C. The lower limit is preferably 0° C. or higher, more preferably 10° C. or higher.

[0035] ((Meth)acrylic resin) There are no particular limitations on the (meth)acrylic resin, and a wide variety of resins made of (meth)acrylic copolymers known as film components for film-like adhesives can be used. The (meth)acrylic resin may be a poly(meth)acrylic acid ester or a derivative thereof, such as a copolymer containing 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, acrylic acid, methacrylic acid, itaconic acid, glycidyl methacrylate, or glycidyl acrylate as a monomer component. Also preferred are copolymers using, as monomers, (meth)acrylic acid esters having a cyclic skeleton, such as (meth)acrylic acid cycloalkyl esters, (meth)acrylic acid benzyl esters, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and imide (meth)acrylate. Also preferred as monomer components are (meth)acrylic acid alkyl esters in which the alkyl group has 1 to 18 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, and butyl (meth)acrylate. It may also be copolymerized with vinyl acetate, (meth)acrylonitrile, styrene, etc. The (meth)acrylic resin preferably has a hydroxyl group in terms of compatibility with the epoxy resin.

[0036] The weight average molecular weight of the (meth)acrylic copolymer is preferably 10,000 to 2,000,000, and more preferably 100,000 to 1,500,000. By setting the weight average molecular weight within the above preferred range, tackiness can be reduced and an increase in melt viscosity can be suppressed. The glass transition temperature of the (meth)acrylic copolymer is preferably in the range of −35° C. to 50° C., more preferably −10° C. to 50° C., still more preferably 0° C. to 40° C., and particularly preferably 0° C. to 30° C. By setting the glass transition temperature within the above preferred range, tackiness can be reduced and the occurrence of voids between the semiconductor wafer and the film-like adhesive, for example, can be suppressed.

[0037] (Polyurethane resin) The polyurethane resin is a polymer having a urethane (carbamic acid ester) bond in the main chain. The polyurethane resin has a structural unit derived from a polyol and a structural unit derived from a polyisocyanate, and may further have a structural unit derived from a polycarboxylic acid. The polyurethane resin may be used alone or in combination of two or more kinds. The Tg of the polyurethane resin is usually 100° C. or less, preferably 60° C. or less, more preferably 50° C. or less, and also preferably 45° C. or less.

[0038] The weight average molecular weight of the polyurethane resin is not particularly limited, and one within the range of 5,000 to 500,000 is usually used.

[0039] The polyurethane resin can be synthesized by a conventional method, and can also be obtained from the market. Examples of commercially available products that can be used as the polyurethane resin include Dynaleo VA-9320M, Dynaleo VA-9310MF, and Dynaleo VA-9303MF (all manufactured by Toyochem Co., Ltd.).

[0040] The content of the polymer component (C) relative to 100 parts by mass of the epoxy resin (A) is preferably 1 to 40 parts by mass, more preferably 5 to 35 parts by mass, and even more preferably 10 to 30 parts by mass. By setting the content within such a range, it is possible to adjust the rigidity and flexibility of the thermally conductive film-like adhesive before curing. The film condition becomes good (film tackiness is reduced), and film brittleness can also be suppressed.

[0041] <Nitride ceramic filler (D)> The nitride ceramic filler (D) is a powder of nitride ceramics, and is not particularly limited as long as it is a nitride ceramic filler that satisfies the above-mentioned conditions (1) to (3). The nitride ceramic filler (D) contributes to imparting thermal conductivity to the adhesive composition and the film-like adhesive. Examples of the nitride ceramic include aluminum nitride, boron nitride, silicon nitride, etc. From the viewpoint of increasing thermal conductivity, aluminum nitride is preferred. The nitride ceramic filler (D) is preferably a pulverized / crushed product obtained by subjecting a nitride ceramic filler to a pulverization / crushing treatment described below.

[0042] The thermal conductivity of the nitride ceramic filler (D) is not particularly limited, and is preferably 12 W / m·K or more, more preferably 30 W / m·K or more, even more preferably 50 W / m·K or more, and even more preferably 100 W / m·K or more. When the thermal conductivity of the nitride ceramic filler (D) is equal to or greater than the above-mentioned preferred lower limit, the amount of the nitride ceramic filler (D) to be mixed in order to obtain the target thermal conductivity can be reduced, and as a result, the increase in the melt viscosity of the adhesive film can be further suppressed, the ability to embed the film into the uneven parts of the substrate when the film is pressed against the substrate can be further improved, and the occurrence of voids can be further suppressed. In the present invention, the thermal conductivity of the nitride ceramic filler (D) means the thermal conductivity at 25° C., and the literature value of each material can be used. Even if there is no description in the literature, the value measured according to JIS R 1611 can be used instead. In addition, when the nitride ceramic filler (D) has thermal conductivity anisotropy and exhibits different thermal conductivities in a plurality of directions, the highest thermal conductivity is regarded as the thermal conductivity of the nitride ceramic filler.

[0043] The nitride ceramic filler (D) may be surface-treated or surface-modified. Examples of the agent or compound (collectively referred to as a surface treatment agent) used for such surface treatment or surface modification include a silane coupling agent, phosphoric acid or a phosphoric acid compound, a surfactant, and the like. In addition to the matters described in this specification, for example, the description of the silane coupling agent, phosphoric acid or a phosphoric acid compound, and a surfactant in the section on thermally conductive fillers in International Publication No. 2018 / 203527 or the section on aluminum nitride fillers in International Publication No. 2017 / 158994 can be applied. In addition, when a surface-treated or surface-modified nitride ceramic filler (D) is used in the present invention, the above conditions (1) to (3) are satisfied in the surface-treated or surface-modified state.

[0044] Methods for mixing the nitride ceramic filler (D) with resin components such as the epoxy resin (A), the epoxy resin curing agent (B) and the polymer component (C) include a method in which a powdered nitride ceramic filler and, if necessary, a silane coupling agent, phosphoric acid or a phosphoric acid compound, a surfactant, etc. are directly mixed with the resin component (integral blend method), or a method in which a slurry of the nitride ceramic filler (D) in which the nitride ceramic filler (D) treated with a surface treatment agent such as a silane coupling agent, phosphoric acid or a phosphoric acid compound, a surfactant, etc. is dispersed in an organic solvent is blended with the resin component. In addition, the method for treating the nitride ceramic filler (D) with a silane coupling agent, phosphoric acid or a phosphoric acid compound, a surfactant, etc. is not particularly limited, and examples thereof include a wet method in which the nitride ceramic filler (D) is mixed with a silane coupling agent, phosphoric acid or a phosphoric acid compound, a surfactant, etc. in a solvent, a dry method in which the nitride ceramic filler (D) is treated with a silane coupling agent, phosphoric acid or a phosphoric acid compound, a surfactant, etc. in a gas phase, and the integral blend method described above.

[0045] In particular, aluminum nitride particles contribute to high thermal conductivity, but are prone to generating ammonium ions through hydrolysis, so it is preferable to use them in combination with a phenolic resin with a low moisture absorption rate, or to suppress hydrolysis through surface modification. As a method for modifying the surface of aluminum nitride particles, a method is particularly preferable in which an aluminum oxide layer is provided on the surface layer to improve water resistance, and the surface is treated with phosphoric acid or a phosphoric acid compound to improve affinity with resin. It is also preferable to use an ion trapping agent in combination.

[0046] The silane coupling agent is a compound in which at least one hydrolyzable group such as an alkoxy group or an aryloxy group is bonded to a silicon atom, and in addition, an alkyl group, an alkenyl group, or an aryl group may be bonded. The alkyl group is preferably one substituted with an amino group, an alkoxy group, an epoxy group, or a (meth)acryloyloxy group, and more preferably one substituted with an amino group (preferably a phenylamino group), an alkoxy group (preferably a glycidyloxy group), or a (meth)acryloyloxy group. Examples of the silane coupling agent include 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropylmethyldimethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-methacryloyloxypropylmethyldimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropylmethyldiethoxysilane, and 3-methacryloyloxypropyltriethoxysilane.

[0047] The surface treatment agent such as a silane coupling agent, phosphoric acid or a phosphoric acid compound, a surfactant, etc. is preferably contained in an amount of 0.1 to 2.0 parts by mass per 100 parts by mass of the nitride ceramic filler (D). By setting such a ratio, it is possible to suppress the aggregation of the nitride ceramic filler (D) while suppressing the volatilization of the excess silane coupling agent, surfactant, etc. during the semiconductor assembly heating process (e.g., the reflow process) and thus to suppress the occurrence of peeling at the adhesive interface, thereby improving the adhesiveness.

[0048] In addition to the nitride ceramic filler (D), the adhesive composition of the present invention may also contain an inorganic filler other than the nitride ceramic filler. Examples of such inorganic fillers include inorganic fillers that are commonly used in adhesive compositions. The nitride ceramic filler is preferably 70 mass % or more of the total amount of the filler, more preferably 80 mass % or more, and even more preferably 90 mass % or more. In the adhesive composition of the present invention, the total amount of the filler may be the nitride ceramic filler (D).

[0049] <Other additives> In addition to the epoxy resin (A), the epoxy resin curing agent (B), the polymer component (C) and the nitride ceramic filler (D), the adhesive composition of the present invention may further contain additives such as organic solvents (methyl ethyl ketone (MEK) and the like), ion trapping agents (ion trapping agents), curing catalysts, viscosity modifiers, antioxidants, flame retardants, colorants, butadiene rubbers, silicone rubbers and other stress relaxation agents, within the scope of the invention. For example, the description of other additives in International Publication No. 2017 / 158994 can be applied.

[0050] The total content of the epoxy resin (A), epoxy resin curing agent (B), polymer component (C) and nitride ceramic filler (D) in the adhesive composition of the present invention is not particularly limited as long as the film-like adhesive of the present invention can be obtained, but it can be, for example, 60 to 95 mass%, and preferably 70 to 90 mass%. The adhesive composition of the present invention can be suitably used to obtain a film-like adhesive of the present invention. However, the adhesive composition is not limited to a film-like adhesive, and can also be suitably used, for example, in a liquid adhesive.

[0051] The adhesive composition of the present invention can be obtained by mixing the above-mentioned components at a temperature at which the epoxy resin (A) does not actually cure. The order of mixing is not particularly limited. For example, the resin components such as the epoxy resin (A) and the polymer component (C) may be mixed together with a solvent as necessary, and then the nitride ceramic filler (D), the epoxy resin curing agent (B) and the silane coupling agent may be mixed. In this case, the mixing in the presence of the epoxy resin curing agent (B) may be performed at a temperature at which the epoxy resin (A) does not actually cure, and the mixing of the resin components in the absence of the epoxy resin curing agent (B) may be performed at a higher temperature.

[0052] From the viewpoint of making the nitride ceramic filler (D) satisfy the conditions (1) to (3), the method for producing an adhesive composition of the present invention preferably includes a pulverization / crushing treatment step of the nitride ceramic filler. The pulverization / crushing treatment step may be a step including at least one of a pulverization treatment or a crushing treatment of the nitride ceramic filler. The conditions of the pulverization / crushing treatment may be appropriately set so that the obtained nitride ceramic filler satisfies the above conditions (1) to (3). The crushing / disintegration treatment can be carried out using a crushing / disintegrating machine such as a jet mill, a bead mill, a hammer mill, or a roller mill. The conditions for the pulverization and crushing treatment are appropriately set according to the nitride ceramic filler and the treatment machine used. For example, when treatment is performed using a jet mill, conditions (1) to (3) can be achieved with high efficiency when the treatment volume is 7 to 9 kg / hr and the nozzle pressure is 0.6 to 0.8 MPa. When treatment is performed using a bead mill, conditions (1) to (3) can be achieved with high efficiency when the bead material is zirconia-based, the bead particle size is 1.5 mm in diameter, the bead packing rate is 70%, the feed amount is 0.8 to 1.0 L / hr, the auxiliary is ethanol, and the mill peripheral speed is 4.0 m / s.

[0053] <Characteristics of film adhesive> (Melt Viscosity) When a film-like adhesive obtained using the adhesive composition of the present invention (hereinafter also referred to as the film-like adhesive of the present invention) is heated from 25°C at a rate of 5°C / min, the melt viscosity at 70°C is preferably in the range of 15000 to 50000 Pa·s. This melt viscosity at 70°C is more preferably in the range of 15000 to 45000 Pa·s, even more preferably in the range of 15000 to 40000 Pa·s, and particularly preferably in the range of 16000 to 36000 Pa·s. By having the melt viscosity at 70°C within the above preferred range, it is possible to further reduce the generation of voids between the semiconductor wafer and the film-like adhesive when the film-like adhesive is bonded to the semiconductor wafer. Furthermore, when the film-like adhesive of the present invention is heated from 25°C at a rate of 5°C / min, the melt viscosity at 120°C is preferably in the range of 500 to 10,000 Pa·s. This melt viscosity at 120°C is more preferably in the range of 800 to 9,000 Pa·s, even more preferably in the range of 1,000 to 8,000 Pa·s, even more preferably in the range of 1,500 to 6,000 Pa·s, even more preferably in the range of 1,500 to 4,000 Pa·s, and particularly preferably in the range of 1,500 to 3,000 Pa·s. By having the melt viscosity at 120°C within the above preferred range, it is possible to further reduce the generation of voids between the uneven portions of the wiring board when a semiconductor chip provided with the film-like adhesive is thermocompression bonded to the wiring board. In the present invention, the above melt viscosity is obtained by measuring the change in viscous resistance of the thermally conductive film-like adhesive before heat curing at a temperature range of 25 to 200° C. and at a temperature rise rate of 5° C. / min from 25° C. using a rheometer (product name: RS6000, manufactured by Haake), and calculating the melt viscosities at 70° C. and 120° C. from the obtained temperature-viscosity resistance curve. Specifically, the measurement method described in the Examples can be referred to. Here, the thermally conductive film-like adhesive before heat curing in the measurement of melt viscosity means a thermally conductive film-like adhesive that has not been exposed to temperature conditions of 25° C. or higher for one month or more. The melt viscosity can be adjusted within the above range by the content of the nitride ceramic filler (D) and further the type of the nitride ceramic filler (D), as well as the types and contents of coexisting compounds or resins such as the epoxy resin (A), the epoxy resin curing agent (B) and the polymer component (C).

[0054] (Thermal Conductivity) The film-like adhesive of the present invention preferably has a thermal conductivity of 1.0 W / m·K or more after thermal curing. The thermal conductivity is more preferably 1.5 W / m·K or more. If the thermal conductivity is less than the above-mentioned preferable lower limit, it tends to be difficult to dissipate the generated heat to the outside of the package. Since the film-like adhesive of the present invention exhibits such excellent thermal conductivity after thermal curing, a semiconductor package with improved heat dissipation efficiency to the outside of the semiconductor package can be obtained by adhering the film-like adhesive of the present invention to an adherend such as a semiconductor wafer or wiring board and thermally curing it. The upper limit of thermal conductivity is not particularly limited, but in reality it is no more than 7.0 W / m·K, more preferably no more than 6.5 W / m·K, and also preferably no more than 5.0 W / m·K. Therefore, the thermal conductivity of the film-like adhesive of the present invention after thermal curing is preferably 1.0 to 7.0 W / m·K, more preferably 1.5 to 6.5 W / m·K, and even more preferably 1.5 to 5.0 W / m·K. Here, "after thermal curing" in the measurement of thermal conductivity means a state in which the curing of the thermosetting resin is completed, specifically, a state in which no reaction heat peak is observed when a DSC (differential scanning calorimeter) measurement is performed at a temperature rise rate of 10°C / min. In the present invention, the thermal conductivity of the film-like adhesive after heat curing refers to the value obtained by measuring the thermal conductivity by the heat flow meter method (based on JIS-A1412) using a thermal conductivity measuring device (product name: HC-110, manufactured by Eiko Seiki Co., Ltd.) For specific details, the measurement method described in the examples can be referred to. In order to set the thermal conductivity within the above range, the content of the nitride ceramic filler (D) and further the type of the nitride ceramic filler (D) can be adjusted by the types and contents of coexisting compounds or resins such as the epoxy resin (A), the epoxy resin hardener (B) and the polymer component (C). The film-like adhesive of the present invention also has insulating properties as a characteristic.

[0055] <<Film adhesive and its manufacturing method>> The thermally conductive film-like adhesive of the present invention is a film-like adhesive obtained from the adhesive composition of the present invention, and contains the above-mentioned epoxy resin (A), epoxy resin curing agent (B), polymer component (C) and nitride ceramic filler (D). In addition, the adhesive composition of the present invention may contain additives other than the organic solvent among the additives described as other additives.

[0056] More specifically, the thermally conductive film-like adhesive of the present invention is specified as follows. A thermally conductive film-like adhesive comprising an epoxy resin (A), an epoxy resin curing agent (B), a polymer component (C) and a nitride ceramic filler (D), The nitride ceramic filler (D) satisfies the following conditions (1) to (3), A thermally conductive film-like adhesive, in which the proportion of the nitride ceramic filler (D) in the total content of the epoxy resin (A), the epoxy resin curing agent (B), the polymer component (C) and the nitride ceramic filler (D) is 25 to 65 volume %. (1) The average particle size determined by image analysis is 0.1 to 2.5 μm. (2) The image analysis circularity is 0.7 or more. (3) The maximum particle size determined by image analysis is 10.0 μm or less.

[0057] When the film-like adhesive of the present invention is formed using an adhesive composition containing an organic solvent, the solvent is usually removed from the adhesive composition by drying. Therefore, the content of the solvent in the film-like adhesive of the present invention is 1000 ppm or less (ppm is based on mass), and usually 0.1 to 1000 ppm. Here, in the present invention, the term "film" refers to a thin film having a thickness of 200 μm or less. The shape, size, etc. other than the thickness are not particularly limited and can be appropriately adjusted according to the mode of use. The film-like adhesive of the present invention is in a pre-cured state, i.e., in a B-stage state. The film-like adhesive of the present invention can be suitably used as a die attach film in the semiconductor manufacturing process.

[0058] The thickness of the film-like adhesive of the present invention is not particularly limited, but is preferably 1 to 200 μm, and from the viewpoint of being able to be more fully embedded in the unevenness of the wiring board and the semiconductor chip surface, is more preferably 1 to 100 μm, further preferably 1 to 50 μm, more preferably 1 to 40 μm, and also preferably 1 to 30 μm, also preferably 1 to 20 μm, and also preferably 1 to 10 μm. The thickness is also preferably 2 μm or more, and also preferably 3 μm or more (i.e., in each of the preferred ranges of the thickness, the lower limit may be 2 μm, and is also preferably 3 μm). By controlling the thickness of the film-like adhesive as described above, for example, when used as a die attach film, it can be more fully embedded in the unevenness of the wiring board or the semiconductor chip surface, and can also be excellent in thermal conductivity. In addition, the organic solvent can be sufficiently removed during production, and a form exhibiting moderate film tackiness can be obtained. The thickness of the film adhesive is a value measured by a contact linear gauge method (desktop contact thickness measuring device).

[0059] The film-like adhesive of the present invention can be formed by preparing the adhesive composition (varnish) of the present invention, applying this composition onto a release-treated substrate film, and drying as necessary. The adhesive composition usually contains an organic solvent. The release-treated base film may be any film that functions as a cover film for the resulting film-like adhesive, and any known film may be appropriately used. For example, release-treated polypropylene (PP), release-treated polyethylene (PE), and release-treated polyethylene terephthalate (PET) may be mentioned. As the coating method, a known method can be appropriately adopted, and examples thereof include methods using a roll knife coater, a gravure coater, a die coater, a reverse coater, and the like. The drying may be performed by removing the organic solvent from the adhesive composition to form a film-like adhesive without curing the epoxy resin (A), and may be performed, for example, by maintaining the composition at a temperature of 80 to 150°C for 1 to 20 minutes.

[0060] The film-like adhesive of the present invention may be composed of the film-like adhesive of the present invention alone, or may be in a form in which the above-mentioned release-treated substrate film is laminated to at least one surface of the film-like adhesive. Furthermore, it may be in the form of a dicing die attach film integrated with a dicing film. The film-like adhesive of the present invention may be in the form of a film cut to an appropriate size, or may be in the form of a film wound into a roll.

[0061] <<Semiconductor package and its manufacturing method>> Next, preferred embodiments of the semiconductor package and its manufacturing method of the present invention will be described in detail with reference to the drawings. In the following description and drawings, the same or corresponding elements are given the same reference numerals, and duplicated explanations will be omitted. Figures 1 to 7 are schematic vertical cross-sectional views showing a preferred embodiment of each step of the manufacturing method of the semiconductor package of the present invention.

[0062] In the method for manufacturing a semiconductor package of the present invention, first, as a first step, as shown in FIG. 1, the film-like adhesive (die attach film) of the present invention is thermocompression bonded to the back surface (i.e., the surface of the semiconductor wafer 1 on which no semiconductor circuit is formed) of a semiconductor wafer 1 having at least one semiconductor circuit formed on its surface to provide an adhesive layer 2 (film-like adhesive 2) (lamination step), and then a dicing film 3 is provided via the adhesive layer 2 (film-like adhesive 2). In FIG. 1, the film-like adhesive 2 is shown smaller than the dicing film 3, but the size (area) of both films is appropriately set depending on the purpose. Thermocompression bonding is performed at a temperature at which the epoxy resin (A) is not substantially thermoset. For example, conditions of 70°C and a pressure of 0.3 MPa can be mentioned. As the semiconductor wafer 1, any semiconductor wafer having at least one semiconductor circuit formed on its surface can be used as appropriate, and examples thereof include a silicon wafer, a SiC wafer, and a GaS wafer. There are no particular limitations on the device used when providing the film-like adhesive 2 of the present invention on the back surface of the semiconductor wafer 1, and for example, known devices such as a roll laminator or manual laminator can be used as appropriate. In the above, the die attachment film and the dicing film are attached separately, but when the film adhesive of the present invention is in the form of a dicing die attachment film, the film adhesive and the dicing film can be attached together.

[0063] Next, in the second step, as shown in FIG. 2, the semiconductor wafer 1 and the adhesive layer 2 are diced simultaneously to obtain a semiconductor chip 5 with an adhesive layer on a dicing film 3, the semiconductor chip 4 being formed by dividing the semiconductor wafer 1 and an adhesive piece 2 being formed by dividing the film-like adhesive 2. There is no particular limitation on the dicing film 3, and any known dicing film may be used as appropriate. Furthermore, there is no particular limitation on the device used for dicing, and any known dicing device may be used as appropriate.

[0064] Next, in the third step, the semiconductor chip with the adhesive layer is peeled off from the dicing film. At this time, the dicing film may be cured with energy rays to reduce adhesive strength, if necessary. The peeling can be performed by picking up the semiconductor chip 5 with the adhesive layer. Next, as shown in FIG. 3, the semiconductor chip 5 with the adhesive layer and the wiring board 6 are thermocompression bonded via the adhesive piece 2, and the semiconductor chip 5 with the adhesive layer is mounted on the wiring board 6 (die attach step). As the wiring board 6, a board having a semiconductor circuit formed on its surface can be appropriately used, for example, a printed circuit board (PCB), various lead frames, and a board having electronic components such as resistor elements and capacitors mounted on its surface.

[0065] There are no particular limitations on the method for mounting the semiconductor chip 5 with an adhesive layer on such a wiring board 6, and any conventional method can be appropriately adopted that can use the adhesive piece 2 to bond the semiconductor chip 5 with an adhesive layer to the wiring board 6 or to an electronic component mounted on the surface of the wiring board 6. Examples of such mounting methods include conventionally known heating and pressurizing methods, such as a method using a mounting technique that uses a flip chip bonder with a heating function from above, a method using a die bonder with a heating function only from below, and a method using a laminator.

[0066] In this way, by mounting a semiconductor chip 5 with an adhesive layer on a wiring board 6 via an adhesive piece 2 made of the film-like adhesive of the present invention, the adhesive piece 2 can be made to conform to the unevenness on the wiring board 6 caused by electronic components, making it possible to fix the semiconductor chip 4 and the wiring board 6 in close contact with each other.

[0067] Next, in the fourth step, the adhesive strip 2 is thermally cured. The temperature for heat curing is not particularly limited as long as it is equal to or higher than the heat curing initiation temperature of the film-like adhesive of the present invention, and can be appropriately set depending on the types of epoxy resin (A), polymer component (C), and epoxy resin curing agent (B) used. For example, 100 to 180°C is preferable, and from the viewpoint of curing in a shorter time, 140 to 180°C is more preferable. If the temperature is lower than the heat curing initiation temperature, the heat curing does not proceed sufficiently, and the strength of the adhesive layer 2 tends to decrease, while if the temperature exceeds the upper limit, the epoxy resin, curing agent, additives, etc. in the film-like adhesive tend to volatilize during the curing process and foam easily. The time for the curing treatment is preferably, for example, 10 to 120 minutes.

[0068] In the method for manufacturing a semiconductor package of the present invention, as shown in Fig. 4, it is preferable to connect a wiring board 6 and a semiconductor chip 5 with an adhesive layer via a bonding wire 7. There are no particular limitations on the method for such connection, and any conventionally known method, such as a wire bonding method or a TAB (Tape Automated Bonding) method, can be appropriately adopted.

[0069] Also, multiple semiconductor chips can be stacked by thermocompression bonding and thermosetting another semiconductor chip 4 on the surface of the mounted semiconductor chip 4, and then connecting it to the wiring board 6 again by wire bonding. For example, there is a method of stacking the semiconductor chips by shifting them as shown in Fig. 5, or a method of stacking them while embedding bonding wires 7 by thickening the adhesive piece 2 for the second and subsequent layers as shown in Fig. 6.

[0070] In the method for producing a semiconductor package of the present invention, as shown in Fig. 7, it is preferable to seal the wiring board 6 and the semiconductor chip 5 with an adhesive layer by a sealing resin 8, and thus a semiconductor package 9 can be obtained. There is no particular limitation on the sealing resin 8, and any suitable known sealing resin that can be used in the production of semiconductor packages can be used. In addition, there is no particular limitation on the method for sealing with the sealing resin 8, and any suitable known method can be adopted. The semiconductor package of the present invention is produced by the above-mentioned method for producing a semiconductor package, and at least one location between the semiconductor chip and the wiring board, or between the semiconductor chips, is bonded with a thermoset product of the film-like adhesive of the present invention. EXAMPLES

[0071] The present invention will be described in more detail below based on examples and comparative examples, but the present invention is not limited to the following examples. Room temperature means 25°C, MEK is methyl ethyl ketone, IPA is isopropanol, and PET is polyethylene terephthalate.

[0072] <Measurement of average particle size, circularity, and maximum particle size by image analysis of nitride ceramic filler> This was done by the method described above.

[0073] <Measurement of specific surface area> 0.8 g of each nitride ceramic filler was thermally dried in an oven at 200°C for 10 minutes, and the specific surface area was measured using a BET single-point method with a He:N2 = 3:7 mixed gas using a Macsørb Model HM-1210 specific surface area meter.

[0074] <Melt Viscosity Measurement> A square measuring 5.0 cm long x 5.0 cm wide was cut out from the film-like adhesive with release film obtained in each Example and Comparative Example, the release film was peeled off, the laminated pieces were laminated, and the pieces were laminated with a hand roller on a hot plate with a stage of 70°C to obtain a test piece with a thickness of approximately 1.0 mm. The test piece was heated from 25°C to 250°C at a rate of 5°C / min using a rheometer (RS6000, manufactured by Haake) to measure the change in viscous resistance. The melt viscosities (Pa s) at 70°C and 120°C were calculated from the obtained temperature-viscosity resistance curves.

[0075] <Lamination evaluation> The film-like adhesive with release film obtained in each Example and Comparative Example was first adhered to one side of a dummy silicon wafer (8 inch size, thickness 50 μm) using a manual laminator (product name: FM-114, manufactured by Technovision) at a temperature of 70° C. and a pressure of 0.1 MPa or 0.3 MPa. The presence or absence of voids at the interface between the film-like adhesive and the wafer after adhesion was visually observed from the film-like adhesive side, and lamination properties were evaluated based on the following evaluation criteria. Voids are more likely to occur under adhesion conditions of 0.1 MPa pressure than 0.3 MPa pressure. - Evaluation Criteria - AA: No voids were observed under the pressure condition of 0.1 MPa. A: At least one void is observed under a pressure of 0.1 MPa, but no voids are observed under a pressure of 0.3 MPa. B: 1 to 4 voids are observed under the pressure condition of 0.3 MPa. C: Five or more voids are observed under the pressure condition of 0.3 MPa.

[0076] <Wear volume evaluation> The film-like adhesive with release film obtained in each Example and Comparative Example was first bonded to a dummy silicon wafer (8 inch size, 100 μm thick) using a manual laminator (product name: FM-114, manufactured by Technovision) at a temperature of 70° C. and a pressure of 0.3 MPa. After that, the release film was peeled off from the film-like adhesive, and then a dicing film (product name: K-13, manufactured by Furukawa Electric Co., Ltd.) and a dicing frame (product name: DTF2-8-1H001, manufactured by DISCO) were bonded to the surface of the film-like adhesive opposite the dummy silicon wafer using the same manual laminator at room temperature and a pressure of 0.3 MPa. Dicing was performed to a size of 1.0 mm x 1.0 mm under the following processing conditions using a dicing device (product name: DFD-6340, manufactured by DISCO) equipped with a two-axis dicing blade (Z1: NBC-ZH2030-SE (DD), manufactured by DISCO, Z2: NBC-ZH127F-SE (BB), manufactured by DISCO). This dicing process was repeated until the length of the film-like adhesive reached 150 m. Setup was performed before dicing (before processing) and at the point of cutting 150 m (after processing), and the blade tip exposure was measured using a non-contact method (laser method), and the blade wear amount after processing (blade tip exposure amount before processing - blade tip exposure amount after processing) was calculated. The calculated amount was evaluated according to the following evaluation criteria. - Processing conditions - Cutting depth into dicing film: 30μm Cutting speed: 30mm / sec Rotational speed: 40,000 rpm - Evaluation Criteria - AA: Wear amount less than 10 μm A: Wear volume is 10μm or more and less than 20μm B: Abrasion amount is 20 μm or more and less than 30 μm C: Wear amount is 30μm or more

[0077] <Die attachment evaluation> The film-like adhesive with release film obtained in each Example and Comparative Example was first adhered to one side of a dummy silicon wafer (8 inch size, 100 μm thick) using a manual laminator (product name: FM-114, manufactured by Technovision) at a temperature of 70° C. and a pressure of 0.3 MPa. After that, the release film was peeled off from the film-like adhesive, and then a dicing film (product name: K-13, manufactured by Furukawa Electric Co., Ltd.) and a dicing frame (product name: DTF2-8-1H001, manufactured by DISCO) were adhered to the surface of the film-like adhesive opposite the dummy silicon wafer using the same manual laminator at room temperature and a pressure of 0.3 MPa. Next, dicing was performed from the dummy silicon wafer side to a size of 10 mm x 10 mm using a dicing device (product name: DFD-6340, manufactured by DISCO) equipped with a two-axis dicing blade (Z1: NBC-ZH2050 (27HEDD), manufactured by DISCO; Z2: NBC-ZH127F-SE (BC), manufactured by DISCO), to obtain dummy chips. Next, the dummy chip with the film-like adhesive was picked up from the dicing film using a die bonder (product name: DB-800, manufactured by Hitachi High-Technologies Corporation), and the film-like adhesive side of the dummy chip with the film-like adhesive was bonded to the mounting surface side of a lead frame substrate (42Alloy type, manufactured by Toppan Printing Co., Ltd.) by thermocompression bonding under conditions of 120°C, pressure of 0.05 MPa (load 200 gf) or 0.1 MPa (load 400 gf), and time of 1.0 second. Here, the mounting surface of the lead frame substrate was a metal surface with slight surface roughness. The dummy chip with the film-like adhesive thermocompression bonded onto the substrate was observed for the presence or absence of voids at the interface between the film-like adhesive and the lead frame substrate using an ultrasonic flaw detector (SAT) (FS300III, manufactured by Hitachi Power Solutions), and the die attachment performance was evaluated based on the following evaluation criteria. - Evaluation Criteria - AA: No voids were observed in any of the 24 semiconductor chips mounted at a pressure of 0.05 MPa. A: Not applicable to the above AA, but no voids were observed in any of the 24 semiconductor chips mounted at a pressure of 0.1 MPa. B: Not applicable to the above AA and A, but voids were observed in 1 to 3 of the 24 semiconductor chips mounted at a pressure of 0.1 MPa. C: Not applicable to the above AA, A, or B, but voids were observed in 4 or more of the 24 semiconductor chips mounted at a pressure of 0.1 MPa.

[0078] <Thermal conductivity evaluation> A square piece with one side of 50 mm or more was cut out from the film-like adhesive with release film obtained in each Example and Comparative Example, and the square pieces were overlapped with the release film peeled off to obtain a sample with a thickness of 5 mm. This sample was placed on a disk-shaped mold with a diameter of 50 mm and a thickness of 5 mm, and heated at 150°C and a pressure of 2 MPa for 10 minutes using a compression press molding machine, removed, and then further heated in a dryer at 180°C for 1 hour to thermally cure the film-like adhesive. In this way, a disk-shaped test piece with a diameter of 50 mm and a thickness of 5 mm was obtained. The thermal conductivity (W / (m·K)) of this test piece was measured by the heat flow meter method (in accordance with JIS-A1412) using a thermal conductivity measuring device (product name: HC-110, manufactured by Eiko Seiki Co., Ltd.).

[0079] <Preparation of nitride ceramic filler> The particle size and other properties of the nitride ceramic filler used in each of the Examples and Comparative Examples were controlled by subjecting the following nitride ceramic filler to a pulverization and crushing treatment under the following conditions. (Nitride ceramic filler) AlN1: HF-01 (product name), aluminum nitride, manufactured by Tokuyama Corporation AlN2: A-01-F-WR2 (product name), aluminum nitride, manufactured by Maruwa Co., Ltd. AlN3: TFZ-A02P (product name), aluminum nitride, manufactured by Toyo Aluminum Co., Ltd. AlN4:H grade (product name), aluminum nitride, manufactured by Tokuyama Corporation BN1: UHP-S1 (product name), boron nitride filler, manufactured by Showa Denko (Crushing and crushing processing) 10 kg of each of the above nitride ceramic fillers was placed in a table feeder (model number: S type, manufactured by Seishin Enterprise Co., Ltd.) and crushed and disintegrated in a jet mill crusher and disintegrator (model number: FS-4 type, manufactured by Seishin Enterprise Co., Ltd.) at a processing rate of 8.0 kg / hr and a nozzle pressure of 0.7 MPa.

[0080] The image analysis average particle size, image analysis circularity, image analysis maximum particle size, and specific surface area of ​​each nitride ceramic filler before and after the above-mentioned crushing / disintegration treatment are summarized in Table 1 below.

[0081] [Table 1]

[0082] Hereinafter, for convenience, each nitride ceramic filler before the crushing / disintegration treatment and each nitride ceramic filler after the crushing / disintegration treatment are distinguished by adding "a" and "b" to the end of the above reference numerals. For example, "AlN1" before the crushing / disintegration treatment is described as "AlN1a", and "AlN1" after the crushing / disintegration treatment is described as "AlN1b".

[0083] <Examples and Comparative Examples> The adhesive compositions and film-like adhesives of the Examples and Comparative Examples were obtained as follows.

[0084] Example 1 A resin varnish was obtained by heating and stirring 55.5 parts by mass of a cresol novolac type epoxy resin (trade name: EOCN-104S, weight average molecular weight: 5000, softening point: 92°C, solid, epoxy equivalent: 218g / eq, manufactured by Nippon Kayaku Co., Ltd.), 48.5 parts by mass of a bisphenol A type epoxy resin (trade name: YD-128, weight average molecular weight: 400, softening point: less than 25°C, liquid, epoxy equivalent: 190g / eq, manufactured by Shin-Nihon Kagaku Epoxy Manufacturing Co., Ltd.), and 120 parts by mass (30 parts by mass as polyurethane resin) of a polyurethane resin solution (trade name: Dynaleo VA-9310MF, weight average molecular weight: 120000, Tg: 39°C, solvent: MEK / IPA mixed solvent, manufactured by Toyochem Co., Ltd.) at a temperature of 110°C for 2 hours in a 1000 ml separable flask. Next, this resin varnish was transferred to an 800 ml planetary mixer, and 252 parts by mass of AlN1b (HF-01 after crushing and disintegration treatment) was added as a nitride ceramic filler, 2.0 parts by mass of an epoxy resin curing agent (product name: 2PHZ-PW, imidazole type curing agent, manufactured by Shikoku Kasei Co., Ltd.) and 3.0 parts by mass of a silane coupling agent (product name: S-510, manufactured by JNC Corporation) were added, and the mixture was stirred and mixed at room temperature for 1 hour, and then degassed under vacuum to obtain a mixed varnish (adhesive composition). The resulting mixed varnish was then applied onto a 38 μm thick release-treated PET film (release film) and dried by heating at 130° C. for 10 minutes to form a film-like adhesive 300 mm long, 200 mm wide, and 10 μm thick. In this way, a film-like adhesive with a release film was obtained.

[0085] Example 2 An adhesive composition and a film-like adhesive with a release film of Example 2 were obtained in the same manner as in Example 1, except that 120 parts by mass (30 parts by mass as acrylic resin) of an acrylic polymer solution (product name: S-2060, weight average molecular weight: 500,000, Tg: -23°C, solids content 25% (organic solvent: toluene), manufactured by Toa Gosei Co., Ltd.) was used instead of the polyurethane resin solution in Example 1.

[0086] Example 3 An adhesive composition and a film-like adhesive with a release film of Example 3 were obtained in the same manner as in Example 1, except that 85 parts by mass (30 parts by mass as phenoxy resin) of bisphenol A type phenoxy resin solution (product name: YP-50EK35, weight average molecular weight: 70,000, Tg: 84°C, solids content 35% (organic solvent: MEK), manufactured by Nippon Steel Epoxy Manufacturing Co., Ltd.) was used instead of the polyurethane resin solution in Example 1.

[0087] Example 4 An adhesive composition and a film-like adhesive with a release film of Example 4 were obtained in the same manner as in Example 1, except that 700 parts by mass of AlN1b (HF-01 after pulverization and crushing treatment) was used.

[0088] Example 5 An adhesive composition and a film-like adhesive with a release film of Example 5 were obtained in the same manner as in Example 1, except that 126 parts by mass of AlN1b (HF-01 after pulverization and crushing treatment) was used.

[0089] Example 6 An adhesive composition and a film-like adhesive with a release film of Example 6 were obtained in the same manner as in Example 1, except that 252 parts by mass of AlN2b (A-01-F-WR2 after pulverization and crushing treatment) was used instead of AlN1b in Example 1.

[0090] Example 7 An adhesive composition and a film-like adhesive with a release film of Example 7 were obtained in the same manner as in Example 1, except that 252 parts by mass of AlN3b (TFZ-A02P after crushing and disintegration treatment) was used instead of AlN1b in Example 1.

[0091] Example 8 An adhesive composition and a film-like adhesive with a release film of Example 8 were obtained in the same manner as in Example 1, except that 178 parts by mass of BN1b (UHP-S1 after pulverization and crushing treatment) was used instead of AlN1b in Example 1.

[0092] Comparative Example 1 An adhesive composition and a film-like adhesive with a release film of Comparative Example 1 were obtained in the same manner as in Example 1, except that 252 parts by mass of AlN1a (HF-01 before crushing and disintegration treatment) was used instead of AlN1b.

[0093] Comparative Example 2 An adhesive composition and a film-like adhesive with a release film of Comparative Example 2 were obtained in the same manner as in Example 1, except that 880 parts by mass of AlN1b (HF-01 after pulverization and crushing treatment) was used.

[0094] Comparative Example 3 An adhesive composition and a film-like adhesive with a release film of Comparative Example 3 were obtained in the same manner as in Example 1, except that 95 parts by mass of AlN1b (HF-01 that had been crushed and disintegrated) was used.

[0095] Comparative Example 4 An adhesive composition and a film-like adhesive with a release film of Comparative Example 4 were obtained in the same manner as in Example 6, except that in Example 6, 252 parts by mass of AlN2a (A-01-F-WR2 before crushing and disintegration treatment) was used instead of AlN2b.

[0096] Comparative Example 5 An adhesive composition and a film-like adhesive with a release film of Comparative Example 5 were obtained in the same manner as in Example 7, except that in Example 7, 252 parts by mass of AlN3a (TFZ-A02P before crushing and disintegration treatment) was used instead of AlN3b.

[0097] Comparative Example 6 An adhesive composition and a film-like adhesive with a release film of Comparative Example 6 were obtained in the same manner as in Example 8, except that 178 parts by mass of BN1a (UHP-S1 before crushing and disintegration treatment) was used instead of BN1b.

[0098] Comparative Example 7 An adhesive composition and a film-like adhesive with a release film of Comparative Example 7 were obtained in the same manner as in Example 1, except that 335 parts by mass of AlN4a (H grade before crushing and disintegration treatment) was used instead of AlN1b in Example 1.

[0099] The obtained film-like adhesive with a release film was subjected to the measurement of melt viscosity, evaluation of lamination properties, evaluation of wear amount, evaluation of die attachment properties, and evaluation of thermal conductivity, as described above. The results obtained are shown in Table 2 below, together with the compositions of the adhesive composition and the film-like adhesive.

[0100] [Table 2-1]

[0101] [Table 2-2]

[0102] The blanks in the "polymer component" and "nitride ceramic filler" columns mean that the component is not contained. The "total solid content" is the total amount (parts by mass) of the epoxy resin, polymer component, nitride ceramic filler, epoxy resin curing agent, and silane coupling agent. "Epoxy resin content" refers to the amount of epoxy resin (parts by mass) per 100 parts by mass of the total amount of components that make up the film adhesive (epoxy resin, polymer component, nitride ceramic filler, epoxy resin hardener, silane coupling agent). "Nitride ceramic filler loading amount (vol %)" is the percentage (vol %) of the nitride ceramic filler in the total content of the epoxy resin, the epoxy resin hardener, the polymer component, and the nitride ceramic filler.

[0103] From Table 2 above, we can see the following: The adhesive compositions of Comparative Examples 1 and 4 to 7 use a nitride ceramic filler that does not satisfy at least any one of the conditions (1) to (3). For all of the film-like adhesives with a thickness of 10 μm obtained from these adhesive compositions, voids were observed when bonding to a wafer at a pressure of 0.3 MPa (lamination process) and when bonding to a lead frame substrate at a pressure of 0.1 MPa (die attach process). It is believed that the voids were formed due to the inclusion of coarse particles in the nitride ceramic filler or the generation of aggregates. In Comparative Example 5, the wear amount of the processing blade was 20 μm or more. It is believed that the wear of the processing blade was severe because a nitride ceramic filler that does not satisfy all of the conditions (1) to (3) was used. Comparative Examples 2 and 3 are adhesive compositions using nitride ceramic fillers that satisfy conditions (1) to (3), but the content does not satisfy 25 to 65 volume %. For the film-like adhesive obtained from the adhesive composition of Comparative Example 2, voids were observed during adhesion to a wafer at a pressure of 0.3 MPa (lamination process) and adhesion to a lead frame substrate at a pressure of 0.1 MPa (die attach process). It is believed that voids were more likely to occur due to an increase in melt viscosity. The film-like adhesive obtained from the adhesive composition of Comparative Example 3 had a low thermal conductivity of 0.8 W / m·K and was poor in thermal conductivity. It is believed that this was due to the amount of nitride ceramic filler filled being too small. In contrast, the adhesive compositions of Examples 1 to 8 use nitride ceramic fillers that satisfy all of the conditions (1) to (3). In all of the film-like adhesives with a thickness of 10 μm obtained from these adhesive compositions, no voids were observed when they were bonded to a wafer at a pressure of 0.3 MPa (lamination process) and when they were bonded to a lead frame substrate at a pressure of 0.1 MPa (die attachment process). In addition, all of the cured products showed excellent thermal conductivity of 1.0 W / m·K or more, and the wear of the processing blade was suppressed to less than 20 μm. Thus, it can be seen that the adhesive composition of the present invention, even in the form of a thin film, suppresses the occurrence of voids both during lamination to a wafer and during die attachment, exhibits excellent thermal conductivity, and further suppresses wear of the processing blade. It is found that, in particular, when the melt viscosity at 70°C is in the range of 16000 to 36000 Pa·s, and when the melt viscosity at 120°C is in the range of 1500 to 3000 Pa·s, voids can be further suppressed.

[0104] Although the present invention has been described in conjunction with embodiments thereof, we do not intend to limit our invention to any of the details of the description unless specifically stated otherwise, and believe that the appended claims should be broadly construed without departing from the spirit and scope of the invention as set forth in the appended claims.

[0105] This application claims priority based on Japanese Patent Application No. 2023-029805, filed in Japan on February 28, 2023, the contents of which are incorporated herein by reference as part of the present specification. [Explanation of symbols]

[0106] 1. Semiconductor wafer 2. Film adhesive 3 Dicing film 4. Semiconductor chips 5. Semiconductor chip with adhesive layer 6 Wiring board 7 Bonding Wire 8 Sealing resin 9. Semiconductor Package

Claims

1. A thermally conductive film-like adhesive comprising an epoxy resin (A), an epoxy resin curing agent (B), a polymer component (C) and a nitride ceramic filler (D), The nitride ceramic filler (D) satisfies the following conditions (1) to (3), A thermally conductive film-like adhesive, wherein the proportion of the nitride ceramic filler (D) in the total content of each of the epoxy resin (A), the epoxy resin curing agent (B), the polymer component (C) and the nitride ceramic filler (D) is 25 to 65 volume %. (1) The average particle size as determined by image analysis is 0.1 to 2.5 μm. (2) The image analysis circularity is 0.75 to 1.

0. (3) The maximum particle size determined by image analysis is 10.0 μm or less.

2. 2. The thermally conductive film-like adhesive according to claim 1, wherein the film-like adhesive has a melt viscosity of 15,000 to 50,000 Pa·s at 70° C. when the temperature of the film-like adhesive is increased from 25° C. at a rate of 5° C. / min.

3. 2. The thermally conductive film-like adhesive according to claim 1, wherein the film-like adhesive has a melt viscosity of 500 to 10,000 Pa·s at 120° C. when the temperature of the film-like adhesive is increased from 25° C. at a rate of 5° C. / min.

4. The thermally conductive film-like adhesive according to claim 1 , which provides a cured product having a thermal conductivity of 1.0 W / m·K or more after thermal curing.

5. The thermally conductive film-like adhesive according to claim 1, having a thickness of 1 to 10 μm.

6. A method for producing a thermally conductive film-like adhesive according to any one of claims 1 to 5, comprising subjecting a nitride ceramic filler to a pulverization / crushing treatment to turn the nitride ceramic filler into the nitride ceramic filler (D) that satisfies the above conditions (1) to (3), and using this nitride ceramic filler (D) to obtain the thermally conductive film-like adhesive.

7. A dicing / die attach film obtained by laminating a dicing film and the thermally conductive film-like adhesive according to any one of claims 1 to 5.

8. A semiconductor package comprising a semiconductor chip and a wiring board, or semiconductor chips bonded together with a thermoset of the thermally conductive film-like adhesive according to any one of claims 1 to 5.

9. A first step of thermocompressing the thermally conductive film-like adhesive according to any one of claims 1 to 5 onto a back surface of a semiconductor wafer having at least one semiconductor circuit formed on a front surface thereof to provide an adhesive layer, and providing a dicing film via the adhesive layer; a second step of dicing the semiconductor wafer and the adhesive layer together to obtain a semiconductor chip with an adhesive layer on the dicing film, the semiconductor chip comprising an adhesive piece and a semiconductor chip; a third step of peeling the semiconductor chip with the adhesive layer from the dicing film and thermocompression bonding the semiconductor chip with the adhesive layer and a wiring substrate via the adhesive piece; a fourth step of thermally curing the adhesive layer; A method for manufacturing a semiconductor package, comprising:

10. 10. The method for manufacturing a semiconductor package according to claim 9, wherein the first step is a step of thermocompression bonding the dicing die attach film according to claim 7 to the back surface of the semiconductor wafer.

Citation Information

Patent Citations

  • Adhesive composition for electronic equipment and adhesive sheet for electronic equipment using the same

    JP2007254527A

  • Flip chip type semiconductor rear face film and use of the same

    JP2012033638A

  • Composition for high thermal conductivity film-like adhesive, high thermal conductivity film-like adhesive, and semiconductor package and method for manufacturing the same using the adhesive

    JP2012207222A

  • Interlayer filler composition for three-dimensional integrated circuit, coating liquid, and method for producing the three-dimensional integrated circuit

    JP2013185124A

  • Adhesive film, tape for working semiconductor wafer, semiconductor package and method for manufacturing the same

    JP2018188540A